Blood–Brain Barrier Permeability Study of Potential Neuroprotective Compounds Recovered From Plants and Agri-Food by-Products - Sánchez-Martínez, José David; Valdés, Alberto; Gallego, Rocio; Suárez-Montenegro, Zully Jimena; Alarcón, Marina; Ibañez, Elena; Alvarez-Rivera, Gerardo; Cifuentes, Alejandro (Frontiers in Nutrition, 2022)
Plants and agri-food by-products represent a wide and renewable source of bioactive compounds with neuroprotective properties. In this research, various green extraction techniques were employed to recover bioactive molecules from Kalanchoe daigremontiana (kalanchoe), epicarp of Cyphomandra betacea (tamarillo), cooperage woods from Robinia pseudoacacia (acacia) and Nothofagus pumilio (lenga), as well as a reference extract (positive control) from Rosmarinus officinalis L. (rosemary). The neuroprotective capacity of these plant extracts was evaluated in a set of in vitro assays, including enzymatic (acetylcholinesterase (AChE), butyrylcholinesterase (BChE) and lipoxygenase (LOX)) as well as antioxidant (ABTS, reactive oxygen and nitrogen species (ROS and RNS)) bioactivity tests. Extracts were also submitted to a parallel artificial membrane permeability assay mimicking the blood–brain barrier (PAMPA-BBB) and to two cell viability assays in HK-2 and SH-SY5Y cell lines. Comprehensive phytochemical profiling based on liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (LC-qTOF-MS) analysis showed enriched content in phenolic and terpenoid compounds in the target extracts. Moreover, in vitro bioactivity tests showed promising neuroprotective capacity, especially for supercritical-fluid extraction (SFE) extract from acacia (ABTS IC50 = 0.11 μg mL−1; ROS IC50 = 1.56 μg mL−1; AChE IC50 = 4.23 μg mL−1; BChE IC50 = 1.20 μg mL−1; LOX IC50 = 4.37 μg mL−1), whereas PAMPA-BBB assays reveal high perfusion capacity of some representative compounds such as phenolic acids or flavonoids. Regarding cytotoxic assays, tamarillo and rosemary SFE extracts can be considered as non-toxic, acacia SFE extract and lenga pressurized liquid extraction (PLE) extract as mild-cytotoxic, and kalanchoe as highly toxic extract. The obtained results demonstrate the great potential of the studied biomass to be transformed into valuable food additives, food supplements or nutraceuticals with promising neuroprotective properties.